ANALYSIS OF COLUMN AND SLAB BEHAVIOR DUE TO ELEVATION DIFFERENCE ON SLOPING GROUND - Dominikus Ola Ama; Sempurna Bangun; Kristina Sembiring; Pio Ranap Tua Naibaho (University Muhammadiyah Jakarta, 2025)
The construction of the I-Smart Building is planned on a site with steep slope topography, with an elevation difference of approximately 8 meters between the front side (+110.000) and the rear side (+102.000), resulting in a slope gradient of about 4.7%. During the construction phase, the zero elevation of the I-Smart Building had to be adjusted to match that of the previously constructed Technopole building, necessitating soil excavation of up to ±5 meters. This adjustment significantly impacted the structural design, particularly due to the variation in column heights, which led to the short column effect. Short columns are known to experience greater shear forces and bending moments due to concentrated lateral loads, while carrying smaller axial loads compared to taller columns. The analysis showed that short columns received approximately 53% higher shear forces and 83% higher bending moments, but carried only half the axial load of tall columns. Nevertheless, all column types satisfied the requirements for cross-sectional capacity, internal forces, and reinforcement needs. Additionally, the difference in column heights affected the distribution of lateral loads on the floor slabs. However, theoretical calculations and structural analysis indicated that the floor slabs were capable of resisting the resulting internal forces, with reinforcement meeting the requirements of SNI 2847-2019. Overall, both the column structures and floor slabs were deemed safe and met design criteria.Keywords: Short Column, Sloped Terrain, Slab, Sloping